Plastome evolution and phylogenomics of Trichosporeae (Gesneriaceae) with its morphological characters appraisal - Cui, Yan-Fang; Zhou, Peng; Xiang, Kun-Li; Zhang, Qiang; Yan, Hua; Zhang, Li-Guo; Pan, Bo; Huang, Yu-Song; Guo, Zhi-You; Li, Zhen-Yu; Xiang, Xiao-Guo (Frontiers in Plant Science, 2023)
Trichosporeae is the largest and most taxonomically difficult tribe of Gesneriaceae due to its diverse morphology. Previous studies have not clarified the phylogenetic relationships within this tribe on several DNA markers, including the generic relationships within subtribes. Recently, plastid phylogenomics have been successfully employed to resolve the phylogenetic relationships at different taxonomic levels. In this study, plastid phylogenomics were used to explore the relationships within Trichosporeae. Eleven plastomes of Hemiboea were newly reported. Comparative analyses, phylogeny and morphological character evolution within Trichosporeae were conducted on 79 species representing seven subtribes. The Hemiboea plastomes range from 152,742 bp to 153,695 bp in length. Within Trichosporeae, the sampled plastomes range from 152,196 bp to 156,614 bp and GC content from 37.2% to 37.8%. A total of 121–133 genes were annotated in each species, including 80–91 protein-coding genes, 34–37 tRNA genes, and 8 rRNA genes. The contraction and expansion of IR borders were not detected, and gene rearrangements and inversions did not occur. The 13 hypervariable regions were proposed as the potential molecular markers for species identification. A total of 24,299 SNPs and 3,378 indels were inferred, and most of the SNPs were functionally missense and silent variations. There were 1968 SSRs, 2055 tandem repeats and 2802 dispersed repeats. The RSCU and ENC values indicated that the codon usage pattern was conserved in Trichosporeae. Both the phylogenetic frameworks based on the whole plastome and 80 CDSs were basically concordant. The sister relationships between Loxocarpinae and Didymocarpinae were confirmed, and Oreocharis was a sister group of Hemiboea with high support. The morphological characters showed a complex evolutionary pattern of Trichosporeae. Our findings may contribute to future research on genetic diversity, morphological evolutionary patterns, and conservation of the tribe Trichosporeae.